Pharmacy On-Site Overdose Protocols and Prevention of Overdose. Issue 1 (December 2022) - Green, Traci C.; Soipe, Ayorinde; Baloy, Brianna; Burstein, Dina; Xuan, Ziming; Tapper, Abigail; Walley, Alexander Y.; Case, Patricia; Bratberg, Jeffrey; Baird, Janette
Background: Opioid overdose is a preventable injury leading to high morbidity and premature mortality in communities across the United States. Overdoses take place where people use drugs, including commercial and public locations like community pharmacies, and necessitate swift detection and response to avoid harm and, even more seriously, death. The presence of emergency and safety protocols improves occupational health and safety for all in the workplace. The aim of this study was to assess the prevalence of experience with on-site pharmacy overdose and to explore pharmacist and site characteristics associated with having a known protocol for responding to on-site overdose emergencies. Methods: An anonymous, online survey about naloxone provision and opioid safety was delivered by email, through professional pharmacy associations and continuing education attendance lists, to 3, 100 pharmacists in Massachusetts and Rhode Island between October 2017 and January 2018. Survey items gauged socio-demographics, practice site characteristics, safer opioid dispensing and naloxone provision. Summary statistics and bivariate analyses were conducted to describe characteristics associated with items pertaining to on-site overdose policy awareness. Results: Of the 357 respondents (11.5% response rate), 154 (5.0%) answered the questions of interest: 17.5% reported having at least one suspected overdose on-site at their practice location, while 42.9% reported that they were knowledgeable about and could locate at their practice location an on-site overdose protocol detailing how to respond to an overdose. Pharmacists who were knowledgeable about protocols were also more likely to offer naloxone to patients ( p = 0.02) and did not practice at a chain pharmacy ( p = 0.01). Conclusions: Community pharmacies that stock and distribute naloxone are key parts of community efforts to address the opioid crisis. Pharmacies and other healthcare settings should develop and implement on-site overdose response protocols and cultivate a norm of naloxone provision to patients.